UPAYA MENINGKATKAN MINAT BELAJAR SISWA TERHADAP KEARIFAN LOKAL MELALUI MEDIA BIG BOOK BERBASIS PERMAINAN TRADISIONAL PADA MATERI KERAGAMAN BUDAYAKU DI KELAS V - Sunarmi; Romia Hari Susanti, M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve fifth-grade students’ learning interest toward local wisdom through the use of Big Book media based on traditional games in the “My Cultural Diversity” material at SDN Pisangcandi 4 Malang City. The ideal learning process in elementary school should be interactive, enjoyable, and able to connect students with their social and cultural environment. However, classroom observations showed low student enthusiasm, limited participation, and weak interest during cultural diversity lessons. This Classroom Action Research employed the Kemmis and McTaggart model in two cycles involving 24 fifth-grade students. In Cycle I, learning used A3-sized Big Book and traditional games conducted inside the classroom and front terrace, including can-knocking, marbles, hopscotch, dakon, jump rope, and bekel. Limitations in space and media visibility reduced learning effectiveness. In Cycle II, improvements were made using an E-Big Book displayed digitally and wider outdoor learning space with an additional traditional game, musical chairs. Data were collected through observation, questionnaires, and documentation. Results showed a significant increase in students’ learning interest from 63.54% in Cycle I (moderate category) to 91.25% in Cycle II (very high category). The study concludes that Big Book media integrated with traditional games effectively improves students’ learning interest toward local wisdom learning.